Effect of melt viscosity on the ejection force in injection moulds - Pontes, A. J. (2004)
This paper shows data on the ejection force of injection mouldings. The tubular mouldings are pin gated. Two polypropylenes with different melt viscosities (melt flow indices) were investigated. Experimental focus is put on the effect of the holding pressure, mould temperature and the cooling time on the measured ejection force. Pressure and temperature were continuously monitored with transducers during the filling process. The ejection force was directly measured with load cells. The results show that higher viscosity lends to higher ejection force.